Infrared LED irradiation photobiomodulation of oxidative stress in human dental pulp cells - Montoro, L. A. [UNESP]; Turrioni, A. P. S. [UNESP]; Basso, F. G. [UNESP]; Souza Costa, C. A. de [UNESP]; Hebling, J. [UNESP] (Wiley-Blackwell, 2014)
Aim To investigate the effect of infrared light-emitting diode (LED) irradiation on the oxidative stress induced in human dental pulp cells (HDPCs) by lipopolysaccharide (LPS).Methodology Human dental pulp cells (HDPCs) were harvested from sound primary teeth that were near exfoliation. Cells were seeded (10 5 cells cm(-2)) using alpha-MEM supplemented with 10% FBS and after 24 h, were placed in contact with LPS (10 mu g mL(-1) of culture medium). Immediately afterwards, HDPCs were subjected to a single irradiation with an infrared LED (855 nm) delivering different doses of energy (0, 2, 4, 8, 15 or 30 J cm(-2)). For each dose, there was a control group without LPS application. Twenty-four hours after irradiation, groups were tested for nitric oxide (NO) quantification, cell viability (MTT assay) and qualitative assessment of reactive oxygen species (ROS). Data were submitted to Kruskal-Wallis and Mann-Whitney tests (alpha = 0.05).Results Lipopolysaccharide (LPS)-induced stress resulted in significant increase in NO production by HDPC without causing damage to cell respiratory metabolism. Irrespective of energy dose delivered, NO production was significantly reduced when LPS-stressed cells were irradiated with infrared LED (2 J cm(-2), P = 0.003; 95% CI = 5.84-27.71; 4 J cm(-2), P = 0.001; 95% CI = 7.52-26.39; 8 J cm(-2), P = 0.0195; 95% CI = -2.86-16.01; 15 J cm(-2), P = 0.0001; 95% CI = 12.10-30.96; 30 J cm(-2), P = 0.007; 95% CI = 5.84-24.71). The highest decrease in NO production was observed when 15 J cm(-2) was delivered to cells. Infrared LED irradiation resulted in a decrease in ROS production, whilst HDPC metabolism was not significantly affected.Conclusion Biomodulation of oxidative stress of HPDC can be achieved by irradiation with a single dose of infrared LED. Within the range investigated, 15 J cm(-2) resulted in the least production of NO.
Keywords: cells cultured; lipopolysaccharides; nitric oxide; phototherapy; reactive oxygen species; spectrophotometry infrared